Komposisi dan struktur komunitas parasitoid hymenoptera antara kebun kopi yang dikelola secara organik dan konvensional di Kabupaten Aceh Tengah - Syukur Hamdi; Sapdi Sapdi; Husni Husni (Jurnal Floratek, 2015)
Composition and Community Structure Hymenoptera Parasitoid Garden Maintained by Conventional and Organic Coffee In District Aceh TengahABSTRACT. This study aimed to obtain scientific information about the species or group of parasitoids associated with habitat, so as to build a database for the purposes of pest management in the future. This research was conducted in coffee plantations in Central Aceh District and continued identification in Pest Laboratory, Faculty of Agriculture UNSYIAH from June to November 2014. This study used a survey method. Insect sampling done by purposive sampling method on coffee plantations were managed conventionally and organically. Abundance of individuals, the number of families and species richness highest Hymenoptera encountered in the practice of organic farming over conventional coffee. Hymenoptera parasitoids composition of coffee plantations are managed organically composed of 13 families, while the coffee plantations were managed conventionally only 7 families. However, Hymenoptera parasitoid community structure on both habitat types are relatively the same because it is dominated by the families Braconidae and Ichneumonidae.